The Effect of Drinking a Cup of Arabica or Robusta Coffee with Sugar or Bread to Blood Sugar Response and Glycemic Index - Umar Hafidz Asy'ari Hasbullah; Fafa Nurdyansyah; Rini Umiyati; Laela Nur Rokhmah (Jurnal Aplikasi Teknologi Pangan, 2021)
The two most widely traded coffee varieties in the world are arabica and robusta. Consumption of these two varieties will increase the intake of bioactive compounds in the human body. However, the influence of consumption of both coffee varieties on blood sugar response and changes in the glycemic index of sugar added when consuming coffee has not been studied. The aim of this research to study the effect of coffee varieties on bioactive compound content, voluntary blood glucose response, and changes in the glycemic index value of sugar when consumed together with coffee. This study was designed with the treatment of arabica and robusta coffee varieties. Coffee roasting was carried out at the level of vienna roasting. Analysis of bioactive compounds was carried out on the content of phenol compounds. Analysis of blood sugar and glycemic index responses using volunteers. Coffee was brewed at a dose of 12 grams per 100 ml of water at 98ᵒC. Sugar added 50 grams. The results showed that arabica contained phenol compounds greater than robusta. It was also prove that consuming coffee can reduce blood glucose response compared to consuming glucose. Decreased blood glucose response of arabica is greater than robusta. Drinking coffee mixed with sugar or with eating bread can reduce the sugar or bread glycemic index value. Decrease in sugar or bread glycemic index value in arabica consumption was greater than robusta. Conclusion, coffee consumption can reduce the response of blood sugar and glycemic index of sugar added to drinks and bread glycemic index because of the content of its bioactive compounds.